Cross-sectional study on the relationship between the Mediterranean Diet Score and blood lipids - Mertens, Evelien (BioMed Central, 2014)
BACKGROUND: Blood lipids are cardiovascular health indicators. High LDL cholesterol values and/or high total cholesterol (TC)/HDL cholesterol ratios are positively related with cardiovascular mortality. Evidence suggests that a Mediterranean diet can reduce the incidence of cardiovascular diseases. Adherence to the Mediterranean diet is often measured by the Mediterranean Diet Score (MDS). However, the association between the Mediterranean diet and blood lipid profiles seems still inconclusive. The aim of this study was to investigate the relationship between the MDS, its different components and blood lipid profiles. METHODS: A sample of 506 women and 707 men (aged 18–75 years) was recruited. Three-day diet records were used to calculate the MDS. Blood samples were analyzed for serum TC, LDL and HDL cholesterol. ANOVA was used to analyze blood lipids across the MDS tertiles. A multivariate linear regression analysis was performed to investigate the associations between the MDS, its components and blood lipids, adjusted for several confounders. All analyses were stratified by gender. RESULTS: Few gender-specific associations were found between the MDS, its components and blood lipids. Only in men, the total MDS was negatively related with LDL cholesterol and the ratio TC/HDL cholesterol while positively with HDL cholesterol. In women, respectively two (MUFA/SFA and cereals) and in men three (fruits & nuts, meat and alcohol) of the nine MDS components were related with blood lipids. CONCLUSIONS: Analyses investigating the relationship between the MDS, its components and blood lipid profiles indicate only limited influence of the Mediterranean diet on blood lipids. More associations were detected in men compared to women.